EDUKASI SENAM REMATIK TERHADAP PENINGKATAN PENGETAHUAN MANAJEMEN KESEHATAN LANSIA DENGAN RHEUMATOID ARTHRITIS - Lisdahayati Lisdahayati; Zanzibar Zanzibar; M. Agung Akbar; Aria Wibisana (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Musculoskeletal problems that often occur in the elderly such as arthritis and bone disorders because they affect activities that are vital for the elderly. To overcome this, it is necessary to provide information or knowledge in the form of education. One of the education that can be given is by rheumatism gymnastics. This study aims to obtain an overview of the increase in knowledge of the elderly group with rheumatoid arthritis after receiving rheumatic gymnastics education. The research design used a case study approach in 2 groups of elderly people with rheumatoid arthritis which consisted of 3 people in each group. The results of health education research are said to be successful because of an increase in knowledge, in group 1 the elderly before being educated 47% after being educated it increased 73% and in group 2 the elderly before being educated 50% after being educated 80%, There is an effect of health education on changes in the level of knowledge in the group with rheumatoid arthritis problems after rheumatism exercise education. It is hoped that health education on rheumatic gymnastics can increase the knowledge of rheumatoid arthritis sufferers and can be used as an alternative to reduce pain other than taking pharmacological drugs